Strategi dalam Mengembangkan Potensi Wisata Situ Lembang Dano di Desa Cipada - Juwita, Tita; Dienaputra, Reiza D.; Nugraha, Awaludin; Novianti, Evi; Tahir, Rusdin (Jurnal Master Pariwisata (JUMPA); Volume 07, Nomor 02, Januari 2021DO - 10.24843/JUMPA.2021.v07.i02.p04, 2021)
This study aims to find out how the development strategy of Lembang Dano situ in Village of Cipada, and to get the right strategy for the development of Lembang Dano tourist attractions. The data has taken of primary data and secondary data, where primary data is obtained from questionnaires and interviews to predetermined sources and secondary data obtained from agencies and agencies related to this study. The analytical tool used the SWOT analysis method the results of the research show that the development strategy needs to first determine the factors that are strengths and weaknesses (internal environment) ourism potential in Lembang Dano Cipada Village, then combines with the opportunities and threats from outside (external environment). Keywords: development strategy, Tourism, Situ lembang Dano, Village of Cipada